Alcohol Use and Its Socio-Economic and Health Effects in the Tharu Community of Raptisonari Rural Municipality (Voice: A Biannual & Bilingual Journal, 2024)
This study examines the use and effects of alcohol consumption within the Tharu community of Raptisonari Rural Municipality, Banke District, Nepal. Alcohol, classified as a sedative, tranquilizer, hypnotic, or anesthetic based on consumption quantity, is the only drug whose self-induced intoxication is socially acceptable. The Tharu community exhibits a high prevalence of alcohol use, impacting health and socio-economic status. Despite its significance, no comprehensive study has been conducted on this issue within the Tharu community. This research employs a descriptive and quantitative approach, surveying 144 respondents from 200 Tharu households through interviews and observations. The findings reveal that 69.4% of male and 30.6% of female respondents consume alcohol, with significant use starting in teenage years. Home-made alcohol, or Raksi, is predominantly consumed (83.3%), with cultural habits (31.3%) and stress relief (22.9%) being primary motivations. The study highlights several adverse effects, including high blood pressure, family quarrels, low income, and other health issues. The research underscores the urgent need for targeted interventions to address alcohol-related problems in the Tharu community, emphasizing the importance of integrating screening for alcoholism into routine health practices. Understanding these dynamics is crucial for improving health outcomes and socio-economic conditions in the community.